Development and Evaluation of Extreme Value Type-I Unit Hydrograph Model - Rana, R S (Journal of Agricultural Engineering, 2007)
The hydrologic data of 452.25 kmÂ² Chaukhutia watershed of Ramganga reservoir catchment in Uttarakhand was analyzed to develop unit hydrograph model using the extreme value type-I distribution function. The parameters of the model were determined by method of moments. The direct runoff hydrographs were developed by convolving effective rainfall values with one-hour unit hydrograph (1-hUH) for evaluating the prediction performance of the model. The quantitative performance based on statistical measures like coefficient of efficiency and absolute relative error in computed peak flow rates were evaluated in order to test the validity and assess the applicability of the model. The average values of coefficient of efficiency and absolute relative error in computed peak flow rates were found to be 0.9113 and 7.84 per cent respectively. Thus the extreme value type-I unit hydrograph model can be used to simulate the direct runoff hydrographs of Chaukhutia watershed.